Structural Analysis of Carbon Fiber-reinforced Thermoset Composite - Barreiro, Larissa; Araújo, Paulo; Teles, John (International Journal of Engineering and Management Sciences, 2019)
Materials are usually stronger in fibrous form than in bulk form. Composites are made from bonding two materials, where the reinforcement contributes with the outstanding natural properties and the matrix supports the fibers by transferring the loads between them, besides protecting the fiber from the environment hazards. Consequently, creating a strong composite that can be used in various applications and situations. In this academic work it is going to be analyzed how the composite made from carbon fiber and epoxy thermoset matrix behaves in specific situations, by making them in two different manufacturing methods. In addition, the analysis is going to be made in the laboratories of the university and then compared with computer analysis. So, the first phase of this academic work is being presented and highlighted below.